Managing competences : research, practice, and contemporary issues - Grasser, Benoit; Loufrani-Fedida, Sabrina; Oiry, Ewan (London : Taylor & Francis, 2020)
Managing Competences: Research, Practice, and Contemporary Issues draws together theoretical and practical research in competence management. It provides a wealth of knowledge concerning emerging and contemporary issues, such as the multilevel approach to competence, the development of collective competence, the strategies of competence management, and the tools for managing competences as well as the organizational dynamics of competences. Moreover, the book provides a critical approach to research and practitioners' continued engagement in competence management research and practice. Research in competence management has more recently entered an era more open to doubt and questioning: Is there a solid theoretical foundation that supports the concept of competence? What is the contribution of research on employees' competences to human resources management in particular, and more generally to management? Is there not a risk of diluting the concept of competence by considering it at the individual, collective, organizational, and strategic levels? Today, is it still possible to manage competences in a world where the boundaries of the organizations are more and more porous? These questions, and many others, probably explain why a field that seemed well-identified and well-structured yesterday, has given way today to new, highly diverse analyses of competences by researchers and practitioners. This contributed volume seeks to answer these pressing issues and is a collective means for responding to them. The book brings together multiple streams of research in the field about emerging and contemporary issues, including multidimensional HRM systems, the rise of forms of collaborative management, the intensification of the use of digital and robotic technologies, the rise of the regime of remote and networked operations, the increasing heterogeneity of the status of workers, and changes in regulations concerning work and its recognition.
OCLC-licensed vendor bibliographic record.
Keywords: Management; Performance; Organization; BUSINESS & ECONOMICS / Human Resources & Personnel Management; BUSINESS & ECONOMICS / Management Science; BUSINESS & ECONOMICS / Project Management